Sistema de gestão da qualidade da energia elétrica em usinas geradoras com análise da contribuição da malha de terra - DANTAS, Jorge Pelaes (Universidade Federal do Pará, 2017)
The abundant electric energy is fundamental to a country’s development, it is the engine which builds its economy, strengthening both big industries, small estabilishments as well as the house consumers, generating jobs, profit and increasing the life quality of its ens. On this contexto, the Energy Quality (QEE) concept arose, whose aim is to study the quality of the provided energy by the electrical facilities like the ones of generation, always searching solutions so that the generated electricity arrives at its final destination with no disturbances, according demands of the control offices. This essay has the main purpose the implantation of a energy quality monitoring system (SMQEE) at the Eletrobrás Eletronorte Coaracy Nunes Hydroelectric Power Plant (UHE) in Amapá State. The constant problems in auxiliary generation components as well as the number of events found by the power plant oscillographs worked as motivation to the implantation of the SMQEE. Besides the SMQEE description developed to the UHE Coaracy Nunes, it will be presented the preliminar results of the data over the power plant energy quality, especially the auxiliary services. The oscillographies data from the oscillographs and tension and current data collect gadgets developed and installed in the ground and auxiliary services, form the SMQEE data bank, from which the checks are made and the reports are extracted from the QEE in the power plant. In this system the oscillography is decomposed by the Wavelet techinque to detect the beginning and the end of the occurences that characterize the QEE events which is meant to extract. The SMQEE proposal is the use of the oscillography to the extraction of thefollowing phenomena: tension harmonics, short range tension variations (tension drownings and elevations, interruptions), tension unbalance and transitories. It will also be processed by the SMQEE the system protection functioning, being available to the analyst the visualization of the state of the protection gadgets, to analyze and diagnosis of the occurrence. As main results it has been noticed that the SMQEE, still in implantation stage, shows to answer the Coaracy Nunes Power Plant work routine demands. In conclusion, we may infer tha the usage of computer programs to the QEE monitoring and analysis are important tools to the prevention of electrical systems problems.